Conflict or compromise : The Future of Public Sector Industrial Relations - Boivin, Jean (Relations Industrielles / Industrial Relations, 1985)
This article reviews the book, "Conflict or compromise : The Future of Public Sector Industrial Relations," by Mark Thompson & Gene Swimmer.